2018
DOI: 10.1002/bjs.10792
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year experience of paediatric thyroid surgery using intraoperative nerve monitoring

Abstract: Continuous IONM measures nerve electrophysiology more accurately than intermittent IONM during thyroidectomy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 22 publications
1
45
0
1
Order By: Relevance
“…Despite the many advantages of ET electrodes, there are also problems in terms of verification, maintenance, stability, patient selection and operative use ( Table S1, supporting information). Proper placement of the ET with complete contact with the mucosa of the vocal cords is essential to minimize monitoring problems, specifically to obtain the best impedance, thus providing a precise EMG profile and exact determination of loss of signal, and allowing differentiation between signal and artefact.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many advantages of ET electrodes, there are also problems in terms of verification, maintenance, stability, patient selection and operative use ( Table S1, supporting information). Proper placement of the ET with complete contact with the mucosa of the vocal cords is essential to minimize monitoring problems, specifically to obtain the best impedance, thus providing a precise EMG profile and exact determination of loss of signal, and allowing differentiation between signal and artefact.…”
Section: Introductionmentioning
confidence: 99%
“…CIONM is thought to reduce permanent vocal fold palsy rates more effectively than IIONM (0% vs. 0.4%; P = .019) because it measures nerve electrophysiology more accurately, and continually verifies functional integrity of the vagus–RLN axis in real‐time. Altogether, CIOMN facilitates reversal of the injurious surgical maneuver associated with the electromyogram (EMG) alteration by alerting the surgeon to impending nerve injury …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Schneider et al reported normative IONM data on children undergoing thyroid surgery, including the impact of age on basal amplitude and latency. 11 To our knowledge, these are the only normative VEMG data available in the literature stratified by age in children. Here, we use the application of VEMG in the chronic injury setting as a new technique offered for better interpretation of neural circuit status.…”
Section: Introductionmentioning
confidence: 98%
“…Intraoperative nerve monitoring (IONM) has gained widespread acceptance during thyroid and parathyroid surgery, with vagal electromyography (VEMG) employed as a useful adjunct . Schneider et al reported normative IONM data on children undergoing thyroid surgery, including the impact of age on basal amplitude and latency . To our knowledge, these are the only normative VEMG data available in the literature stratified by age in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation